2016
DOI: 10.1371/journal.pone.0158069
|View full text |Cite
|
Sign up to set email alerts
|

Facets of Spirituality Diminish the Positive Relationship between Insecure Attachment and Mood Pathology in Young Adults

Abstract: Traditionally, in attachment theory, secure attachment has been linked to parameters of mental health, while insecure attachment has been associated with parameters of psychopathology. Furthermore, spirituality and attachment to God have been discussed as corresponding to, or compensating for, primary attachment experiences. Accordingly, they may contribute to mental health or to mental illness. In this cross-sectional observational study, we investigate attachment styles (Avoidant and Anxious Attachment; ECR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 43 publications
5
26
0
Order By: Relevance
“…For example, substance use disorders have been linked to a deficiency in personality development ( Bernstein et al, 1998 ; Trull et al, 2000 ) emotion regulation ( Goldstein and Volkow, 2011 ) as well as low RSWB ( Unterrainer et al, 2013 ). In addition, a lower RSWB was found to be linked to affective symptoms in non-clinical previous research ( Hiebler-Ragger et al, 2016 ). However, the established bio-psycho-social model of health and disease, first proposed by Engel (1977) , does not include these aspects of religiosity and spirituality.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…For example, substance use disorders have been linked to a deficiency in personality development ( Bernstein et al, 1998 ; Trull et al, 2000 ) emotion regulation ( Goldstein and Volkow, 2011 ) as well as low RSWB ( Unterrainer et al, 2013 ). In addition, a lower RSWB was found to be linked to affective symptoms in non-clinical previous research ( Hiebler-Ragger et al, 2016 ). However, the established bio-psycho-social model of health and disease, first proposed by Engel (1977) , does not include these aspects of religiosity and spirituality.…”
Section: Discussionmentioning
confidence: 61%
“…Understanding the interactions between primary emotions, personality and RSWB could be of particular importance to clinical research, as these dimensions have been discussed in relation to various psychological disorders, e.g., ( Horton et al, 2015 ; Hiebler-Ragger et al, 2016 ; Unterrainer et al, 2017 ). For example, substance use disorders have been linked to a deficiency in personality development ( Bernstein et al, 1998 ; Trull et al, 2000 ) emotion regulation ( Goldstein and Volkow, 2011 ) as well as low RSWB ( Unterrainer et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, several empirical studies showed substantial associations between a prevalent borderline personality organization and SUD ( 44 , 45 ). Interestingly, connections between insecure attachment and symptoms of mood pathology, as well as addiction, can also be found in non-clinical populations ( 46 , 47 ).…”
Section: Introductionmentioning
confidence: 99%